Diagnostic Scoring in Biliary Atresia* - Güngör, Şükrü; Varol, Fatma İlknur; Altundaş, Ebubekir; Gök, Emre; Yıldız, Turan; Demiröz, Sevgi (Turkish Journal of Gastroenterology, 2025)
Background/Aims: The aim of this study was to develop a diagnostic scoring model to predict the need for intraoperative cholangiogra phy in patients with neonatal cholestasis suspected of having biliary atresia (BA) and to aid in the early diagnosis of BA. Materials and Methods: Data from 70 patients with neonatal cholestasis who underwent intraoperative cholangiography with a prelimi nary diagnosis of BA between 2019 and 2024 were retrospectively reviewed. Data from patients with and without BA were compared. Thescoring was based on 3 parameters: acholic stool observed clinically on inspection, findings suggestive of BA on ultrasound, and elevated gamma-glutamyl transferase (GGT) levels. The best GGT cut-off point for the diagnosis of BA was determined by receiver operating characteristic analysis. The diagnostic success of the scoring model for BA was statistically evaluated. Results: There were no significant differences in age and gender between BA and non-BA groups. Gamma-glutamyl transferase levels were elevated in all patients. Acholic stools were present in 98% of BA patients. Ultrasound findings suggestive of BA were present in 88.5% of patients with BA. The authors found the best GGT cut-off value for the diagnosis of BA to be ≥366 (73% sensitivity, 77.8% specificity). In the scoring model the authors developed, the presence of 2 parameters provided diagnostic success with high sensitivity (98%) and specificity (83.3%). Conclusion: The study provides a reliable and sensitive diagnostic criterion to determine the need for intraoperative cholangiography in infants with neonatal cholestasis. These data should be validated in larger prospective case series. Cite this article as: Güngör Ş, Varol Fİ, Altundaş E, Gök E, Yıldız T, Demiröz S. Diagnostic scoring in biliary atresia. Turk J Gastroenterol. 2025;36(11):763-769.